Optimization of Brand Engagement and Loyalty Through Informative Interactivity and Starbucks Indonesia Instagram Social Media Marketing Trends - Su’ada, Riva; Yuniawan, Ahyar (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Social media has become an almost ubiquitous environment for human interaction. As a result, as the use of Social Media becomes more and more common, companies today are trying to reach and interact with customers and prospects through social media platforms. This research examines and develops the influence of Promotion and Social Media on consumer engagement variables through brand performance and their structural relationships, and will provide specific strategic directions to build a strong owned brand in the restaurant sector. Therefore, research on this topic is necessary. We used 100 Starbucks Indonesia consumers as a source of information in this study. The result is that Promotion and Brand Performance have a positive and significant effect on Consumer Engagement. Meanwhile, Social Media has a positive and insignificant effect on consumer engagement with Starbucks Indonesia consumers. The brand promotion has a positive and insignificant effect on the performance of Starbucks Indonesia consumers. Brand Social Media has a positive and significant effect on the performance of Starbucks Indonesia consumers. Other test results using Specific Indirect Effect analysis to prove the influence of the intervening variable Brand Performance proved to be incapable of being an intervening variable between Promotion and Brand Performance. The test results of the Specific Indirect Effect analysis prove that the influence of the intervening variable Brand Performance is proven to be an intervening variable between Social Media and Consumer Engagement.